Is vitamin D supplementation program in Iranian schools effective in reducing adolescent depressive symptoms? Cost effectiveness study - Seyed Vahid Jasemi; Zhale Zandieh; Narges Zandieh; Mohsen Rezaei Hemami; Ali Darvishi; Zahra Abdollahi; Ramin Heshmat (BMC, 2023)
Abstract Purpose We aimed to assess the cost-effectiveness of the vitamin D supplementation program in Iranian adolescents reducing adolescent depressive Symptoms. Methods In the current cost-effectiveness analysis, the viewpoint of Iran's Ministry of Health was selected. The target population was 1,519,762 Iranian high school students (733,657 girls and 786,105 boys). The total costs of the vitamin D supplementations program were based on the reports of the Nutrition Improvement Office of Iran's Ministry of Health and were adjusted to 2018. The variable of Quality-Adjusted Life Years (QALYs) was considered a suitable variable for estimating the effectiveness of vitamin D supplementation. We chose one year as the time horizon. A decision tree model was constructed in TreeAge Pro. The results of the cost-effectiveness analysis were reported in term of the Incremental Cost-Effectiveness Ratio (ICER). Results The results of our study showed that the estimated cost per QALY gained of the vitamin D supplementation program is equal to 1528.6676 $, which indicates that vitamin D supplementation in adolescents(11-18Y) is a cost-effective and a dominant strategy in preventing depression through the cost-saving and QALYs increment compared to the no intervention. Sensitivity analysis showed that the possible variations in vitamin D supplement costs could not alter the results, and vitamin D supplementation may be a predominant and cost-effective strategy to prevent adulthood depression with a 100% probability. Conclusion The national program of vitamin D supplementation among Iranian adolescents was a cost-efficient strategy reducing adolescent depressive Symptoms through the cost-saving and QALYs increment compared to the no intervention.